An alternative to complete banana mat uprooting: assessing the effectiveness of continuous cutting at soil level of all shoots in a mat on speed for corm decay - Ntamwira, J.; Kamira, M.; Ocimati, W.; Bumba, M.; Blomme, Guy (Academic Journals, 2016)
The complete uprooting of diseased mats/fields (CMU) is one of the recommended control options for Xanthomonas wilt of banana. CMU is labour intensive, time consuming and disturbs the soil structure, exposing fields to erosion. CMU often involves exportation of whole plant biomass, affecting soil fertility. The potential of continuous cutting at soil level of all shoots in a mat until complete corm decay in situ as an alternative to CMU was assessed. The first experiment was established using 224 banana mats in their third cropping cycle. All the plants were cut down at soil level, meristems were removed, and sweet potato and bush bean planted. In a repeat experiment with 180 banana mats, a wide range of treatments were applied on top by cutting and removing the apical meristems. These included the: injection of 2,4-D herbicide into the centre of each corm; removal of a cone shaped section from the center of each corm; and creation of a 20 cm deep incision in the center of each corm; in combination with the application of soil or farmyard manure substrate on cut surface. In the first experiment, re-sprouting stopped at 8 months while corms fully decayed after 25 months. Annual intercrops did not influence re-sprouting and corm decay rate. Similar re-sprouting trends occured in the repeat experiment. However, 2,4-D application significantly (P<0.05) lowered decay time, with 12-47% of corms decomposed at 8 months compared with 0-20% in other treatments without 2,4-D. In the 2,4-D treatments, 100% of corms had decomposed compared with 36-80% in other treatments by the 20th month. Deep incisions or cuts did not significantly hasten decomposition. Soil or manure substrate addition had no advantage when compared with the cut surfaces without substrates. A cost-benefit analysis showed a five times higher net income with continuous cutting of re-sprouts when compared with CMU.